Relationship between TEC jumps and auroral substorm in the high-latitude ionosphere - Chernyshov, A. A.; Miloch, W. J.; Jin, Y.; Zakharov, V. I. (Scientific reports, 2020)
The influence of an auroral substorm on the total electron content (TEC) jumps and cycle slips on Global Positioning System (GPS) at high-latitudes is studied. For the first time, optical data from the all-sky imager, as well as interplanetary magnetic field and magnetometer data are used to complete the analysis of the slips occurrence and to monitor the substorm evolution. Two types of slips are considered: (i) instrumental slips including losses in the measured phase of the GPS signal and (ii) sharp TEC variations (TEC jumps) It is demonstrated that the jumps in TEC determined from the GPS signals are mainly related to the auroral particle precipitation that normally occurs during geomagnetic substorms in the polar ionosphere. The GPS frequency L 2 is consistently subject to more slips than frequency L 1 both for quiet and disturbed conditions. The probability of TEC jumps is higher than for cycle slips in phase at frequencies L 1 and L 2 . The maximum of TEC jumps is observed during the recovery phase of the auroral substorm. Our findings are based on a data set obtained for a particular event. A generalization of the obtained numerical estimates to other events requires additional research and further analysis.